INFLUENCE OF BIOTIC AND ABIOTI CFACTORS ON SEASONAL ABUNDANCE OF LEPIDOPTERAN INSECT PESTS ON CASHEW IN CHHATTISGARH, INDIA - SAHU, K.R.; SHUKLA, B. C.; THAKUR, B.S.; PATIL, S. K.; SAXENA, R. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2015)
Cashew (Anacardium occidantale L.) is dollar earning crop of India. But, production of raw nut is not fulfilling the requirement of the processing industries. There are various factors responsible for low yield in cashew, in which the insect pest problem is major one. Rai (1984) has listed 21 species of lepidopterans as leaf feeders of cashew. To study the seasonal occurrence of leaf feeding lepidopteran insect pests a survey was conducted at S.G. College of Agriculture & Research Station, IGKV, Jagdalpur (C.G.) during 2007 and 2008 in randomly selected trees in cashew plantation in the surrounding areas of District Bastar (Chhattisgarh) and their intensities in forest plantation were recorded at Weekly intervals by placing a frame of 1.0 sq. m area on the tree canopy on all the four sides. The leaf caterpillar damage (33.14% mean damage) was noticed throughout the year with relatively higher damage during November-December. The leaf folder was observed (17.14% mean damage) round the year with maximum in November to January. The leaf miner mean damage was observed (9.20%) almost throughout with the peak in November. The leaf and blossom webber appeared (1.54% mean damage) as minor pest but its damage was seen almost round year, while, some insect pests present in cashew plantation as minor pests which were: inflorescence caterpillar (0.28% mean damage) observed during reproductive stage, semilooper appeared intermittently with peak (0.06 numbers) in November-December, slug caterpillar appeared in spring and cooler season. In natural enemies, spiders were prevalent (0.59 mean population) throughout the year feeding upon thrips and lepidopteran larvae. The maximum temperature and evaporation influenced negatively the leaf caterpillar damages; while, relative humidity and vapour pressure (II) had positively correlated. Leaf folder damage was negatively influenced with maximum temperature, minimum temperature, wind velocity and evaporation; whereas, relative humidity correlated positively. The maximum temperature and evaporation negatively correlated with leaf miner; while, relative humidity and vapour pressure (I) influenced positively. Leaf & Blossom Webber damage was correlated negatively with maximum temperature, evaporation and bright sunshine (hours); while, relative humidity influenced positively. The activity of Inflorescence caterpillar was positively influenced with maximum temperature and evaporation; whereas, relative humidity (morning and evening) were negatively correlated. The maximum temperature had significant negative contribution and the vapour pressure (I) had highly significant positive contribution of 31% towards percentage damage of leaf caterpillar. The 33% variation in leaf folder damage was contributed significantly negatively by maximum temperature and significantly positively by evaporation; while, 27% variation contributed positively by rainy days.